2016
DOI: 10.1098/rsif.2015.1046
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic biology and regulatory networks: where metabolic systems biology meets control engineering

Abstract: Metabolic pathways can be engineered to maximize the synthesis of various products of interest. With the advent of computational systems biology, this endeavour is usually carried out through in silico theoretical studies with the aim to guide and complement further in vitro and in vivo experimental efforts. Clearly, what counts is the result in vivo, not only in terms of maximal productivity but also robustness against environmental perturbations. Engineering an organism towards an increased production flux, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 170 publications
(240 reference statements)
0
35
0
2
Order By: Relevance
“…The coordinates of the focal point φ a for region R a can be explicitly calculated recalling (14) and using Def. 6:…”
Section: Focal Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates of the focal point φ a for region R a can be explicitly calculated recalling (14) and using Def. 6:…”
Section: Focal Pointsmentioning
confidence: 99%
“…However, there are no general stability analysis methods that can deal with the type of nonlinearities and connectivity of metabolic systems. A number of recent reviews in metabolic engineering have highlighted the need for model-based approaches for design [3,14,21], while the use of control theoretical principles has gained substantial traction in the field [25,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been established that properly accounting for the activation/inhibition of enzymes by endogenous small molecules can lead to metabolic models that explain experimental data better (Chandra et al, 2011; Hackett et al, 2016; Khodayari and Maranas, 2016; Link et al, 2013; Xu et al, 2012a), facilitate engineering of novel metabolic pathways (Chen et al, 2015; He et al, 2016), and improve our understanding of metabolic phenomena in health and disease (Christofk et al, 2008). So far, high-throughput experimental assays for discovering small molecule regulatory interactions have been technically limited (Feng et al, 2014; Li et al, 2013; Nikolaev et al, 2016; Orsak et al, 2012; Reinhard et al, 2015; Savitski et al, 2014), while hybrid approaches that integrate experimental data with computational models are not scalable and typically focus on central carbon metabolism (Hackett et al, 2016; Link et al, 2014, 2013; Schueler-Furman and Wodak, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In [76], Oyarzú n & Stan provided detailed guidance on the selection of promoters and ribosome binding sites that reflects the trade-offs and constraints of transcriptional feedback for metabolic pathways. More broadly, feedback control has been extensively used in metabolic engineering, which is not the focus of this paper and an indepth review can be found elsewhere [77]. Recently, in addition to transcriptional regulation, the biological toolbox has significantly expanded.…”
Section: Negative Feedback Implementationsmentioning
confidence: 99%